Degree Modification and Pluractionality in Spanish - Padilla-Reyes, Ramon E (Borealis – An International Journal of Hispanic Linguistics, 2018)
Standard and Puerto Rican Spanish has two modifiers, bastante/enough and más/more. These modifiers behave like the Spanish modifier muy/very in that they can modify gradable adjectives. However, these modifiers have an additional property. They are categorically flexible, in that they can combine not only with adjectives but also nouns and verbs. And when they modify verbs, plucational readings emerge. I show that these modifiers convey a multiplicity of pluractional readings that stem from the verb’s lexical property. Also, I show how these modifiers can be syntactically flexible. In the grammar, más and bastante bind to an event variable which determines its semantic. El español puertorriqueño y estándar cuenta con dos modificadores, bastante/enough y más/more. Estos se comportan como el modificador muy/very en que modifica adjetivos gradables. Sin embargo, estos modificadores tienen una propiedad adicional. Son categóricamente flexibles, en que pueden combinar no solamente con adjetivos, pero también con sustantivos y verbos. Y cuando modifican verbos, surge unas interpretaciones de pluraccionales. Demuestro que estos modificadores codifican una multiplicidad de interpretaciones pluraccionales. Estas interpretaciones surgen de las propiedades léxicas del verbo cuyo están modificando. También, demuestro como estos modificadores pueden ser sintácticamente flexibles. En la gramática, más y bastante se enlazan a una variable de eventos el cual determina su semántica.
Keywords: Adverbs; Semantics; Syntax; Gradability; Pluractionality; Spanish